The role of zinc and its compounds in leukemia - Orlov, Alexey P.; Orlova, Marina A.; Trofimova, Tatiana P.; Kalmykov, Stepan N.; Kuznetsov, Dmitry A. (Journal of biological inorganic chemistry, 2018)
Zinc is one of the most important microelements necessary for normal body functioning. Zinc is marked in numerous diseases and, hence, its properties and behavior in the body have long been a subject of extensive study. This review considers trends in the assessment of the role of zinc and its compounds in the past decade. It becomes evident that redox-inactive zinc is the main supervisor in the conformation of the most important molecules in all body organs and tissues. We placed emphasis on the variety of zinc-binding sites and the role of zinc in the genesis and progress of different forms of leukemia. The importance of some families of transcription factors in the development and prognosis of treatment of various leukemia forms is examined; new directions of these studies are shown.